Sentinel‐3A Views Ocean Variability More Accurately at Finer Resolution. Issue 24 (26th December 2017) - Heslop, E. E.; Sánchez‐Román, A.; Pascual, A.; Rodríguez, D.; Reeve, K. A.; Faugère, Y.; Raynal, M.
Abstract: This is the first multiplatform evaluation involving data from the new Sentinel‐3A altimeter. An experiment was undertaken in the Algerian Basin, employing an ocean glider and a ship mission, along the same track and synchronous with an overpass of the Sentinel‐3A mission. This provided three independent views of the ocean velocity field, along a section that encompassed three different oceanographic regimes. The results demonstrate the capacity of Sentinel‐3A to retrieve fine‐scale oceanographic features (~20 km). The intercomparison with in situ platforms showed a significant improvement, order 30% in resolution and 42% in velocity accuracy using a synthetic aperture radar mode with respect to lower‐resolution mode of conventional altimetry. In addition, the three‐platform view provided valuable insight into the variability of evolving oceanographic features, in an area of the Mediterranean that remains chronically under sampled. Key Points: This is the first multiplatform evaluation involving data from the Sentinel‐3A altimeter SRAL sensor New SAR instrument gives an improvement of 42% in the estimation of surface velocities with respect to lower‐resolution altimetry Sentinel‐3A altimeter detects finer‐resolution oceanographic features (reduction of 30%) as compared to previous missions